A comparison between cannulated and non-cannulated cancellous screws used in the fixation of a simulated femoral neck fracture : a finite element study - Du, Zhenglin. (2013)
Femoral neck fractures are a common form of injury amongst the elderly and cannulated screws are the preferred choice for fixation. Previous studies have researched the performance of various screw design and configurations based on pull-out strength as well as the best fixation based on displacement, load and stiffness characteristic. However, little attention was given to the use of finite element method to aid in the investigation of the performance of various fixations. In this study, ABAQUS was used to investigate the performance between cannulated and non-cannulated screws used in an inferior triangular fixation on Pauwel’s type-2 vertical femoral neck fracture with normal Sawbones femur. The von Mises stresses were analysed and the results suggested that the femur with cannulated screws experienced lower stresses.